Enforcement of Health Establishment Act, B.E. 2559 in Thailand - Jungsomjatepaisal, Pattarapol (Journal of Health Science of Thailand, 2020)
This action research aimed to access the achievement of the enforcement of Health Establishment Act, B.E. 2559 and to review its obstacles. Review of the related laws and announcements for the establishment for health service and the minute from supervising board and subcommittee meeting were done. Information from the stakeholders and public via internet was also included. The research results revealed that there were 17 ordinance and regulations were released after the enforcement of Health Establishment Act, B.E. 2559 to reduce the problems associated to the operation following the Act. The health establishment services that had to ask permission to establish included spa, health massage, and beauty massage. There were 7,102 merchants out of 8,293 merchants (85.64%) received the licenses and most of them were health massage. There were 4,105 service managers received the licenses and among them 2,414 used transitional provision licenses; and 87,667 service providers registered for certification to perform the service. In addition, to provide service providers with specified quality, 539 curriculum from 222 educational institutes and other organizations were accredited. The information form the public hearing process with the competent officers, service providers, service managers, and merchants showed that these groups of stakeholder still had many issues related to the Act. According to the research results, the government sectors should precipitate the health establishment service that have not yet received a license must apply for a license urgently and those without a license should be punished with criminal procedures. The educational institutes should be encouraged to develop a qualify curriculum and perform the post gradational evaluation. All of which are to control the quality of education and enhance the quality of the registered providers in accordance with the Medical Hub policy.